2016
DOI: 10.3390/jpm6010002
|View full text |Cite
|
Sign up to set email alerts
|

Building the Partners HealthCare Biobank at Partners Personalized Medicine: Informed Consent, Return of Research Results, Recruitment Lessons and Operational Considerations

Abstract: The Partners HealthCare Biobank is a Partners HealthCare enterprise-wide initiative whose goal is to provide a foundation for the next generation of translational research studies of genotype, environment, gene-environment interaction, biomarker and family history associations with disease phenotypes. The Biobank has leveraged in-person and electronic recruitment methods to enroll >30,000 subjects as of October 2015 at two academic medical centers in Partners HealthCare since launching in 2010. Through a close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(152 citation statements)
references
References 15 publications
1
150
0
1
Order By: Relevance
“…The Partners Biobank is an ongoing virtual cohort study of patients across the Partners HealthCare hospital system (including Brigham and Women's Hospital, Massachusetts General Hospital, and other affiliated hospitals), which provides a large-scale resource of linked longitudinal EHR data, genomic data, and self-reported survey data (Karlson, Boutin, Hoffnagle, & Allen, 2016). All patients provided informed consent before enrollment, and all study procedures were approved by the Partners HealthCare Institutional Review Board.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…The Partners Biobank is an ongoing virtual cohort study of patients across the Partners HealthCare hospital system (including Brigham and Women's Hospital, Massachusetts General Hospital, and other affiliated hospitals), which provides a large-scale resource of linked longitudinal EHR data, genomic data, and self-reported survey data (Karlson, Boutin, Hoffnagle, & Allen, 2016). All patients provided informed consent before enrollment, and all study procedures were approved by the Partners HealthCare Institutional Review Board.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…For example, the Partners Healthcare Biobank is a repository of patient blood samples linked to the EHR and supplemented by survey data capturing data not readily available in the EHR (e.g. sun exposure, family history, and sleep habits) [Karlson and others 2016]. At this writing more than 60,000 patients have enrolled using face-to-face and electronic web-based informed consent [Boutin and others 2016] with approximately 2000 added monthly at Partners hospitals including Massachusetts General Hospital, Brigham and Women’s Hospital, and McLean Hospital.…”
Section: Combining Ehr Data and Genomic Datamentioning
confidence: 99%
“…Previous studies have found that disease specific ICD-codes are registered for patients even if they do not have that disease (54,55). To find the optimal number of ICD codes for patient selection, we explored the ICD code performance in previously reviewed medical records for rheumatoid arthritis in the Partners Biobank (56). Here, one rheumatologist screened the medical records, and assigned case status both by the ACR2010 criteria (14) as well as her expert opinion.…”
Section: Validation Through Simulationmentioning
confidence: 99%